Correlation of Malnutrition with Fall Risk in Elderly: A Systematic Review - Ignasius Adi Dharma; Raden Ayu Tuty Kuswardhani; Nyoman Kertia (CV. Inara, 2025)
Malnutrition is a common health problem among older adults and has the potential to increase the risk of falls, one of the leading causes of morbidity and mortality in this age group. This systematic review aims to analyze the relationship between malnutrition and the risk of falls in older adults by synthesizing findings from eight observational studies. Literature searches were conducted in the PubMed, EBSCO, and Cochrane databases until August 2025. Nutritional status in these studies was assessed using tools such as the Mini Nutritional Assessment (MNA), MUST, and BMI, while the risk of falling was measured using instruments such as the Morse Fall Scale, Johns Hopkins Fall Risk Assessment Tool, Timed Up and Go Test (TUG), and fall history. The results showed a consistent and significant association between malnutrition and an increased risk of falling, with odds ratios ranging from 1.42 to 4.94. These findings were reinforced by biological mechanisms such as sarcopenia and micronutrient deficiencies that impair muscle strength, balance, and neuromuscular function. Based on the GRADE assessment, the level of certainty of the evidence was moderate. Overall, this review confirms that malnutrition is an important and modifiable risk factor, and that routine nutritional screening should be an integral part of fall prevention strategies for older adults.